Absolut Vodka: building consumer bonds - Zaichkowsky, Judy (Henry Stewart Talks, 2020)
This case study uses Absolut Vodka’s Absolut Generations exhibition to demonstrate the creation of consumer bond via ongoing consumer relationships.